PALEONTOLOGICAL AND BIOSTRATIGRAPHICAL CHARACTERISTICS OF THE BADENIAN DEPOSITS ON THE SREBRENIK-DONJA ORAHOVICA PROFILE (BOSNIA AND HERZEGOVINA) - Zijad Ferhatbegović; Amila Avdić; Sumeja Durmić (Rudarsko-geološko-naftni Zbornik, 2022)
The paper describes the biostratigraphic and paleontological research conducted on the geological section of Srebrenik-Donja Orahovica (Northern Bosnia and Herzegovina). The samples for micropaleontological research were taken from the exploration works (eight wells and nine excavations). Based on the presence of microforaminifera, the stratigraphic level of Lower Badenian was defined. According to micropaleontological and biostratigraphic analyzes within this stratigraphic level, one local foraminiferal zone was identified: zone with Trilobatus trilobus and Orbulina suturalis which represents the upper parts of the Lower Badenian. This zone is characterized by a rich microfossil community with a dominance of planktonic forms over benthic ones, normal salinity, warm sea, and basic character of the environment.